Decision Support System Design Structural Promotion Civil Apparatus Using AHP and TOPSIS Methods - Muhamad Yusuf; Kusrini Kusrini; Agung Budi Prasetio (Universitas Raharja, 2021)
The quality of the performance of the State Civil Apparatus (ASN) is a very important resource to be able to determine the capacity of the Regional Apparatus Organization (OPD). One of the efforts to improve the quality of OPD performance is the promotion of positions. Promotion of an award given for work performance and dedication of a civil servant, as well as being excited to improve work performance and loyalty. Therefore, it is necessary to determine a promotion. The weighting method in this study uses the Analytical Hirarchy Process. This study also compares this method with the Technique for Ordering Preference based on Similarities with Ideal Solutions. The resulting criteria are formal and informal. Consists of formal sub-criteria consisting of formal education, position experience, class rank, technical competence, managerial competence and socio-cultural competence. Then for the informal sub-criteria consisting of discipline, innovation, creativity, ideas for institutional functions, the ability to collaborate and work in teams, loyalty, responsibility, leadership, ability to communicate well and recommendations at the provincial and / or ministerial level. Furthermore, calculations are carried out using the AHP and TOPSIS methods for data for 2018 which means 1 position, in 2019 means 2 positions, and in 2020 means 4 positions. In one position consists of 3 ASN alternatives. After comparing the accuracy level of the AHP and TOPSIS methods with experts, the results of the AHP method are better in making recommendations for structural promotion of echelon IV ASN by producing a perfect score of 100% and a TOPSIS value of 71.4%.